Islamic Reform in Contest: Ahmad Hassan and His Traditionalist Opponents - Minhaji, Akh. (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2000)
There is a perception, held not only by scholars in the field but by many Muslims as well, that Islamic law in Indonesia is strongly colored by